Integrating religiosity into fraud triangle theory: Empirical findings from enforcement officers - Said, Jamaliah; Asry, Salsabila; Rafidi, Marhamah; Obaid, Rawia Rida; Alam, Md Mahmudul (Universiti Sultan Azlan Shah, MALAYSIA (USAS), 2018)
Recently, employee-fraud has drawn extensive attention due to huge amount of losses of various organizations.This study developed a new model of fraud risk by integrating new elements into a fraud triangle theory.This study simultaneously analyzed religiosity and the three elements of fraud risk factors of employee fraud committed by low and mid-level public officials.The data collected from 120 enforcement officers indicated that religiosity is negatively related to employee fraud.By contrast, all the three elements of fraud triangle theory, namely, pressure, opportunity, and rationalization, are positively related to employee fraud.These results imply that strong religiosity is crucial to mitigate employee fraud. To minimize employee fraud, the opportunity to commit such fraud should be reduced through strong internal control, reduction of negative rationalization, and employee financial pressure. This study contributes to the literature by introducing a new model on employee-fraud occurrence that is not extensively discussed, particularly in the context of local authority in developing countries.